Immunogenicity of Comirnaty Omicron XBB.1.5 booster COVID-19 mRNA vaccine in long-term survivors after allogeneic hematopoietic stem cell transplantation - Sigrun Einarsdottir; Samer Al-Dury; Ellen Fridriksson; Linn Dahlsten Andius; Hao Wang; Sinan Sharba; Amin Mountagui; Johan Waern; Johan Ringlander; Anna Martner; Kristoffer Hellstrand; Jesper Waldenström; et al. (Scientific Reports)
Abstract Primary mRNA vaccination against COVID-19 typically involves three doses for immunocompromised individuals, including hematopoietic stem cell transplantation (allo-HSCT) recipients. However, optimal subsequent boosting strategies remain unclear. This study aimed to assess the immunogenicity of a booster dose using the most recently updated vaccine (Comirnaty Omicron XBB.1.5) among long-term allo-HSCT survivors having previously received multiple mRNA vaccine doses, in median 4 (2–6). Thirty-four allo-HSCT recipients were enrolled at Sahlgrenska University Hospital, and peripheral blood samples were collected immediately before and four weeks after booster. Antibodies against the receptor-binding domain (anti-RBD) of spike 1 (S1) and nucleocapsid, as well as S1-specific ex vivo T-cell responses, were evaluated. Adverse events were monitored. Despite a median of 13 months since the prior vaccine dose, both humoral and T-cell responses against S1 were present in the pre-booster samples in all but two participants, who suffered from severe chronic Graft-versus-host disease. Notably, 62% of participants had a previously confirmed COVID-19 infection. Significantly higher pre-booster antibody levels were observed in women than men (p = 0.003). Booster dosing strengthened specific antibody and T cell responses and equalized pre-booster gender differences, although responses remained significantly lower among those receiving immunosuppressive treatment (p = 0.041). In a population of long-term allo-HSCT survivors, the majority of whom had a prior confirmed COVID-19 infection, both pre- and post-booster immune responses were robust. However, patients undergoing immunosuppressive treatment for GvHD exhibited significantly weaker responses.